Food safety in Bangladesh: Market characterization and food safety awareness of food vendors and customers - Gazu, Lina; Sharma, Garima; Alonso, Silvia; Samad, M.A.; Begum, R.; Akter, R.; Sinh Dang-Xuan; Islam, S.; Siddiky, N.A.; Uddin, A.S.M.A.; Mahmud, A.; Sarker, M.S.; et al. (International Livestock Research Institute, 2023)
Access to enough safe and nutritious food is a key to sustaining life and promoting good health. Food can however also be a vehicle of disease transmission if contaminated with harmful microbes (bacteria, viruses, or parasites) or chemicals/toxins. Around the world, an estimated 600 million - almost 1 in 10 people – fall ill after eating contaminated food each year, resulting in 420,000 deaths and the loss of 33 million healthy, disability-adjusted life years (DALYs). The WHO South-East Asia Region accounted for 150 million illnesses, 175 000 deaths, and 12 million DALYs in 2010 due to food contamination.